Practices of Sharing & Ways of Knowing. Doing Disability Culture (KULT_online, 2013)
Disability Culture and Community Performance. Find a Strange and Twisted Shape builds on the emerging field of art-as-research and contributes to the shaping of scholarly perspectives on the political potential of community performance and its specific role in disability culture. In this, her most recent book, Petra Kuppers brushes the discussion of theory and the analysis of aesthetic strategies into the background. She adopts an experiential perspective which foregrounds processes of working and being together. Disability Culture and Community Performance is an artist’s book on various creative journeys through diverse cultural and historical settings, but it is also a careful investigation into the methodical consequences emanating from crossings of theory and practice. Furthermore it is an activist intervention and contribution to the doing of disability culture.